The Comparison of Streptokinase, an Old Agent, Versus Reteplase for the Re-Tunnellisation of Blocked Cuffed Haemodialysis Catheter - Saroukhani, Abbas; Omid, Soheil (Scripta Medica, 2024)
Background/Aim: Catheter occlusion is the most common complication occurring in patients with end-stage renal disease (ESRD) who undergo haemodialysis. The management typically involves the use of local fibrinolytic agents. However, with the emergence of novel agents, the use of older agents has declined. The purpose of the study was to compare the effectiveness of reteplase versus streptokinase (SK) in resolving haemodialysis catheter occlusion. Methods: This randomised clinical trial involved 100 patients with catheter occlusion who were equally divided into two groups of 50. One group received treatment with reteplase, while the other group received treatment with SK. The occluded catheter in the first group was instilled with 250,000 units (U) of SK, while the second group received 2 U of reteplase and the catheters were left in place for 2-6 h. Successful flushing of the catheter with a velocity of ≥ 200 rounds per minute was considered successful re-tunnelling. The study also evaluated the frequencies of re-injections and drug-related adverse effects. Results: The success rate of SK versus reteplase did not differ significantly (p = 0.48). However, the required time to inject the agents to achieve appropriate luminal patency was statistically higher in the reteplase-treated group (p = 0.018). None of the patients experienced major adverse effects such as bleeding or anaphylactic reactions. Conclusion: According to the findings of this study, both reteplase and SK resulted in significant recovery of luminal patency with no adverse effects. However, the lower frequency of re-injections required with SK to achieve successful rationalisation favoured the use of this agent over reteplase. Further studies are strongly recommended.